Dynamics Simulation Analysis of a New-type of Planetary Reducer with Few Teeth Difference used by Pumping Unit based on ADAMS - Zhai Cong; Yang Shuncheng; Xiao Xin (Jixie chuandong)
In view of the meshing impact of the gear pairs of the experimental prototype based on the new-type of the planetary reducer with few teeth difference,which is proposed by Xiao Nanping and received the patent for this invention,the three-dimensional model of this reducer established by Solid Works is introduced into the ADAMS to build the model of the virtual prototyping of the reducer.The correctness of this virtual prototype is proved by the simulation of the angular velocity of the input and output shaft and the changing law of the meshing force of the gear pairs with the help of the software ADAMS.And the inertia force caused by the eccentricity of the planet gear has little influence on the meshing force of the gear pairs by comparing the simulation results with the theoretical calculation.And this result can provide the data support for calculating the strength of the gear pairs precisely and analyzing the contact stress of the pairs.